1987
DOI: 10.1017/s0003356100028075
|View full text |Cite
|
Sign up to set email alerts
|

Effects on food intake, rumen development and live weight of calves of replacing barley with sugar beet-citrus pulp in a starter diet

Abstract: Link to this article: http://journals.cambridge.org/abstract_S0003356100028075How to cite this article: P. E. V. Williams, R. J. Fallon, G. M. Innes and P. Garthwaite (1987). Effects on food intake, rumen development and live weight of calves of replacing barley with sugar beet-citrus pulp in a starter diet. Animal Production, 44, pp 65-73 ABSTRACT In three experiments the effects of replacing barley with citrus or unmolassed beet pulp in starter diets for calves was examined. In experiment 1, 40 Friesian bull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 13 publications
0
25
0
2
Order By: Relevance
“…Both high ED feeds ( B and S, defined below) were pelleted. Feed B included 64% ground barley (as-fed basis) as the main dietary carbohydrate; in feed S barley was partially replaced by plain sugar beet pulp ( SBF) , which is fermented more slowly than ground barley (Williams et al, 1987;Van Soest et al, 1991). It was expected that the ingredients used in feeds B and S would create different ruminal fermentation patterns (Sutton et al, 1986).…”
Section: Feedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both high ED feeds ( B and S, defined below) were pelleted. Feed B included 64% ground barley (as-fed basis) as the main dietary carbohydrate; in feed S barley was partially replaced by plain sugar beet pulp ( SBF) , which is fermented more slowly than ground barley (Williams et al, 1987;Van Soest et al, 1991). It was expected that the ingredients used in feeds B and S would create different ruminal fermentation patterns (Sutton et al, 1986).…”
Section: Feedsmentioning
confidence: 99%
“…The second test was to evaluate the influence of the source of carbohydrate in a high ED feed on its selection by sheep, when offered as a choice with a low ED feed, and whether selection would be affected by supplementing the high ED feed with NaHCO 3 . Williams et al (1987) have shown that feeds with a high pectin content (sugar beet pulp, SBF) are consumed in greater quantities than those with a high starch content (barley), and it is presumed this is because feeds based on SBF are associated with a higher ruminal pH than those containing predominantly barley. It was expected that a greater quantity of high ED feed would be selected when it was based on a material such as SBF rather than barley, and that selection of the high ED feed in the chosen diet would increase with NaHCO 3 supplementation.…”
Section: Designmentioning
confidence: 99%
“…Indeed, Harris & Staples (1989) recommend up to 10% of total DM of citrus pulp for animals younger than 60 days. Williams et al (1987) reported an increase in starter intake and average daily gain of milk-fed calves receiving a mixture of citrus pulp and beet pulp instead of barley. Schalch et al (2001) found no differences among treatments for average daily gain, dry matter intake, feed conversion or rumen development when evaluated the replacing of corn grain with 0, 15, 30 or 45% citrus pulp in the starter of milk-fed calves.…”
Section: Introductionmentioning
confidence: 98%
“…Os teores da fração fibra recomendados pelo NRC (2001) Poucos trabalhos são encontrados na literatura avaliando a utilização de polpa cítrica no concentrado de bezerros em aleitamento (Williams et al, 1987, Schalch et al, 2001 Os animais foram pesados ao nascer e semanalmente, sempre antes do aleitamento da manhã, em balança mecânica (ICS-300, Coimma Ltda), até a décima semana de vida, quando se encerrou o período experimental. Foram mensuradas semanalmente, a altura na cernelha e largura da garupa, utilizandose régua com escala em centímetros; e perímetro torácico com fita flexível, também com escala em centímetros.…”
Section: Desaleitamento De Bezerros Leiteirosunclassified